Dziennikarstwo wobec nowych mediów. Szanse i zagrożenia - Głogowski, Tomasz (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Journalism in comparison with new media. Opportunities and threats Journalism has entered a critical period. Print media are losing readers and reducing their circulations at an alarming pace, whereas newspapers are moving to the network, where they face competition with social media. As noted by Paul Levinson, media newer than ‘new media’ have been invented. YouTube, Facebook, Twitter and Wikipedia not only have exerted a huge impact on the surrounding reality, but all it happened in a rapid, difficult to predict manner. A few years ago, some of these services not only did not have a mass audience, but they even did not exist. In this situation the question returned about skills, professional ethos and the way the journalist work in contemporary media. Whether he/she should be merely one of many other providers of information, in the same way as bloggers or people utilising the popular Twitter, or be an insightful analyst of reality, capable of digging up and providing important information. Key words: journalism, media, social media, professional ethos